Marketing Management Analysis of MSME Coto Makassar Restaurant Daeng Memang - Kusumaningrum, Anisa Putri; Swantari, Anita; Ernowo, Atha Fadhil; Wahyuningsih, Tri; Andini, Davi Ayu (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study delves into the marketing strategies of Coto Makassar Daeng Memang, a South Sulawesi restaurant, within Indonesia's evolving culinary landscape. Utilizing Marketing Mix and SWOT analysis, the research unveils the restaurant's evolution, identifying strengths, weaknesses, opportunities, and threats. Coto Makassar's success story, initiated in 1992, unfolds through a diverse menu. The Marketing Mix analysis underscores its affordable products, strategic location, and word-of-mouth promotion. The study concludes by highlighting the critical role of effective marketing for UMKM and the practical insights derived from Coto Makassar Daeng Memang's experience in navigating the competitive Indonesian culinary market.